2019
DOI: 10.1159/000495608
|View full text |Cite
|
Sign up to set email alerts
|

Oral Litholysis in Patients with Chronic Calcific Pancreatitis Unresponsive to or Ineligible for Extracorporeal Shock Wave Lithotripsy and Endoscopic Therapy

Abstract: Background/Aims: Our study aimed to evaluate the effect of oral litholysis in patients with chronic calcific pancreatitis (CCP) unresponsive to or ineligible for extracorporeal shock wave lithotripsy (ESWL) and endoscopic therapy. Methods: Trimethadione, an antiepileptic agent, was administered orally at a dose of 0.6–0.9 g/day to 15 patients with this condition. Treatment outcome was evaluated by assessment of dissolution of the pancreatic stones on plain X-ray films and computed tomography scans of the upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Clinical studies demonstrated that the TMO treatment was effective in dissolving stones, with litholysis or partial litholysis in approximately 86% patients with CCP. [ 23 , 24 ] Additionally, the treatment was highly suggestive of a favorable effect of oral TMO on pancreatic endocrine function and exocrine function in patients whose pancreatic stones were dissolved.…”
Section: Chemical Dissolution Of Pancreatic Stonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies demonstrated that the TMO treatment was effective in dissolving stones, with litholysis or partial litholysis in approximately 86% patients with CCP. [ 23 , 24 ] Additionally, the treatment was highly suggestive of a favorable effect of oral TMO on pancreatic endocrine function and exocrine function in patients whose pancreatic stones were dissolved.…”
Section: Chemical Dissolution Of Pancreatic Stonesmentioning
confidence: 99%
“…Second, if the patients discontinued TMO intake, the pancreatic stones recurred and gradually increased in size and number. [ 24 ] Furthermore, these studies have not been validated and there are no randomized or comparative trials with a large sample size to confirm the efficacy of the proposed treatment.…”
Section: Chemical Dissolution Of Pancreatic Stonesmentioning
confidence: 99%
“…Only isolated case reports have described some drugs, such as citrate and trimethadione, to be potentially useful in dissolving PDS. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%